PERILAKU SOSIAL PEKERJA SEKS KOMERSIAL DI KOTA SURAKARTA - Defi Putri Widyawati; Sudarsana Sudarsana (Journal of Development and Social Change, 2019)
This study was designed to describe the social conversations of callous women in Surakarta. As well as describing the factors that cause women to behave as callous women in Surakarta. This research is a case study using qualitative research. The subjects of the study were prostitutes, adolescent women as college students and single citizens in the Surakarta area as informants. Data collection using the method of observation and interviews in. Researchers are the main research instruments that provide observation guidelines and interview guidelines. Data analysis techniques used are data display, data reduction, and conclusions are drawn. Triangulation used is source triangulation. The results showed that the average informant who was a prostitute woman was still a girl. Regarding the work of the average informant has a main job Although small businesses, because the status as a prostitute woman calls only side. As parents, the average daughter does not know if she has worked as a prostitute. Informant's motivation in working as a prostitute woman on average wants to get more income to meet her needs. In choosing a job as a prostitute woman the average call informant has never had a plan towards being a prostitute woman, and never the status of prostitute women looking for work goals. Actions taken at work, as a tuna woman, and this information is only doubled, within 2 hours can be done to meet their needs for several months. In conducting discussions with coworkers in supermarkets and colleagues in entertainment venues, information on average is not difficult, they can work together, help each other, and foster good relations with one another. The average informant who has fear of the dangers of HIV that befell him. Make them always check their female health to the doctor. The thought of quitting work as immoral women asks all of them to stop because they also understand that this is not good to continue until old age. Factors that can cause informants to plunge into the world of prostitutes are high economic factors.